Comparative literature study of Twak (Skin) according to Ayurveda and Western medicine: Palathiratne S.M.*, Karunatilake L.P.A. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Since, the incidence and impact of diseases of skin are ever increasing; the necessity of proper multifaceted understanding about skin is immense. Furthermore, the knowledge elaborated in Ayurveda and western medicine, if compared in a nutshell, will benefit clinicians vastly. Thus, my objective was to abridge the key facts about Twak (Human Skin) as per both disciplines and for this all relevant literary materials were referred with emphasis to authentic Ayurveda Samhita (Compendiums). Following are some of the notable particulars brought in-to light by this research. Disease conditions of Twak cause physical, mental, social and spiritual disharmonies in a person. Hence, Twak is like a reflector of the total health and wellbeing of an individual and his personality. Thus, treatments of Twak are of paramount importance. The seven layers of Twak proclaimed by Sushruta Samhita, corresponds perfectly with the seven skin layers, accepted by western medicine at present. Sushruta Samhita states that, there is no other worrying disease like Kushtha (Skin Disease) highlighting the suffering of such patient. It is declared by Maharishi (Great Sage) Dhanvantari that, disease Shvitra (Vitiligo) occurs precisely in the fourth layer of Twak; Tamra, which can be accepted even according to modern medicine, since the Melanin pigment is made by copper containing enzyme (Tyrosinase). In conclusion, despite daily advancements and changes in knowledge of western medicine and modern science, the excellence of wisdom proclaimed thousands of years ago by the holy and divine Maharishi of Ayurveda, will stand resolute and unparalleled even in future. Keywords: Twak, Ayurveda, Western Medicine 1Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka. 2Unit of Shalya Shalakya, Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka. *Correspondence: Palathiratne S.M., Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka. Email: palathiratne@yahoo.com